The Development of Leibniz’s Considerations in John Yench’s Project - Kulczycki, Emanuel (University of Bialystok, 2009)
The purpose of the article is to present John Yench’s a priori language as a continuation of Leibniz’s idea. Before I proceed to show the project of the Inter-Disciplinary International Reference Language, I would like to discuss the development of Gottfried Wilhelm Leibniz’s view on artificial languages. I will try to show the evolution of Leibniz’s universal language: from its ideal conception to a tool which formalizes the whole of human knowledge. Also, I will show Leibniz’s influence on further ideas of artificial language. I will compare his projects with Yench’s language – Idirl. An analysis of Idirl’s main assumptions will be useful to show the degree of continuation of Leibniz’s ideas in the a priori language of John Yench.
Keywords: Leibniz; artificial language; philosophy of language; pragmatics; philosophy of language and communication